(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This project focuses on designing an Automatic Speed Control System to enhance road safety by regulating vehicle speed based on environmental conditions and speed limits. Utilizing sensors such as ultrasonic or radar, the system detects obstacles and measures distances, while a GPS module provides location data to identify speed zones. A microcontroller processes this information to adjust the throttle or activate braking, ensuring compliance with speed regulations. Additionally, traffic sign recognition using cameras and machine learning algorithms enables dynamic adaptation to road signs and temporary speed limits. By minimizing human errors such as over speeding and delayed reactions, this system contributes to safer driving, particularly in high-risk zones like school areas and highways. The project demonstrates the practical application of embedded systems in automotive safety, aiming to reduce accidents and promote adherence to traffic laws.